2014
DOI: 10.1016/j.seppur.2014.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on pervaporation separation of aqueous salt solution using hybrid PVA/MA/TEOS membrane

Abstract: Heat treatment is believed to be an important step in controlling the morphology and properties of polymer based membranes. In this study, hybrid organic-inorganic membrane based on poly(vinyl alcohol) (PVA), maleic acid (MA) and tetraethyl orthosilicate (TEOS) was synthesised via a sol-gel route. The effects of heating temperature and heating time on pervaporation separation performance of aqueous salt solution were studied in relation to swelling and hydrophilic properties, the free volume, salt transport pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…As the feed volume used in the system was great enough and any feed concentration variation was negligible throughout the experiment, the apparent diffusion coefficient ( D i ) was calculated from the following equation on the basis of Fick's law: Di=JiδCi where C i is the water concentration on the feed‐side membrane surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the feed volume used in the system was great enough and any feed concentration variation was negligible throughout the experiment, the apparent diffusion coefficient ( D i ) was calculated from the following equation on the basis of Fick's law: Di=JiδCi where C i is the water concentration on the feed‐side membrane surface.…”
Section: Methodsmentioning
confidence: 99%
“…We developed a sol–gel derived unsupported PVA–MA–SiO 2 hybrid organic–inorganic membrane for the separation of an aqueous salt solution . The hybrid membrane showed enhancing effects for the diffusion of water molecules through the membrane and the separation of aqueous salt solution, but the J and mechanical strength were still limited by the nature of the unsupported membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows the effect of temperature on the water uptake properties of the PVA/SiO 2 membranes. Recently, Xie et al [40] reported a significant decrease in the water uptake of PVA/MA/TEOS hybrid membranes from 154 to 43 % when the temperature was raised from 21 to 100°C. However, our PVA/SiO 2 membranes have shown a gradual increase in W u with the increasing temperature, as shown in Fig.…”
Section: Water Uptakementioning
confidence: 99%
“…Likewise, preparation of the hybrid membrane using simultaneous cross-linking of poly (vinyl alcohol) with maleic acid and tetraerthoxysilane for pervaporation desalination applications had been reported. [15][16][17] In another studies, poly (vinyl alcohol) blended with poly (ethylene glycol) 18 or a copolymer of poly (vinyl alcoholco-acrylic acid) 19 was cross-linked with tetraethoxysilane to prepare the hybrid membranes. The cross-linking density of the membrane was found to be increased with increase in the tetraethoxysilane content, annealing temperature and time, which resulted in increment of water permselectivity for pervaporation dehydration of ethanol.…”
Section: Introductionmentioning
confidence: 99%